Effect of cognitive behavioral intervention on physical symptoms, B-type natriuretic peptide, red cell distribution width, C-reactive protein in elderly heart failure patients - Xiaoyan Li; Meixia Zhang; Zepeng Ren; Junfen Deng (Journal of Cardiothoracic Surgery)
Abstract Objective To observe how cognitive behavioral intervention affects physical symptoms, B-type Natriuretic Peptide (BNP), Red Cell Distribution Width (RDW), and C-reactive Protein (CRP) in elderly patients with heart failure. Methods Convenient sampling method was used to select 98 elderly heart failure patients who visited our hospital from January 2022 to December 2020. Patients were divided into a control group and an observation group using the red and blue ball method, with 49 cases in each group. Control group received routine intervention, while observation group received cognitive behavioral intervention on the basis of control group. The changes in the somatosensory scale scores of patients with heart failure before and after routine treatment were recorded. The changes in blood BNP, RDW, and CRP levels were measured before and within 4 weeks, 8 weeks after intervention. Results After intervention, the dimensions and total scores of DHFq scale in observation group were lower than control group’s during the same period (P < 0.05). The total DHFq scale score in observation group improved faster (P < 0.05). Both groups of patients showed a decrease in BNP after intervention compared to before (P < 0.05). The levels of DNP, RDW, and CRP in observation group after intervention were lower than control group’s (P < 0.05). Conclusion Cognitive behavioral intervention for elderly patients with heart failure can alleviate their physical symptoms, promote the improvement of vascular function indicators BNP and RDW, and reduce inflammatory factor CRP in the body, reducing the burden on the healthcare system.